MODEL PEMBERDAYAAN MASYARAKAT EKOLOGIS KULTURAL UNTUK PENYELAMATAN MATA AIR DI KOTA BATU - Susilo, Rachmad K Dwi (JURNAL SATWIKA, 2017)
The construction of the hotel that was opposed by the users of water resource triggered the emergence of social movement. While inititating movement, they initiated the programs of community empowerment as well. It means that the community empowerment is one of strategies of movement. Then, besides focusing on cultural activities, the other activities are the optimization of youth potentials and the care about community activities. In this context, the ecological cultural is joined by the other community interests. This strategy is effective because the empowerment stimulated the development of social network and local culture. The critic of this empowerment is culture is not a central of activities. The culture is still used as instrument for the conservation of environment. This stance is always questioned and criticized by the environmental and cultural activists in Malang Town. This article will describe the model of cultural ecological empowerment in Batu City that is described from the emergence of community empowerment, the forms of the community empowerment, the form of social changes after interventions, and the strengths and weaknesses of this empowerment. This article utilized the descriptive research method with ethnographical approach. Meanwhile, the used sampling is purposive sampling with eight subjects of research are activists of Nawakalam Gemulo, community based organization in Cangar Hamlet, Bulukerto Village, Batu City.